La constitucionalización del derecho administrativo - Landa, César (Pontificia Universidad Católica del Perú, 2016)
The link between Administrative Law and Constitutional Law, branches of Public Law, is undeniable. It is even more patent currently with the phenomenon of the constitutionalization of Law.In this article, the author analyses this phenomenon in the field of Administrative Law, the administrative-constitutional principles, and examines how various institutions of Administrative Law have been constitutionally configurated,outlined and controlled in Peru, for which he goes over the most important jurisprudence of the Peruvian Constitutional Court regarding the matter.

La vinculación entre el Derecho Administrativo y el Derecho Constitucional, ramas del Derecho Público, es incuestionable. Ello es incluso más notorio actualmente con el fenómeno de la constitucionalización del Derecho.  En el presente artículo, el autor analiza este fenómeno en el campo del Derecho Administrativo, los principios constitucionales administrativos, y examina cómo distintas instituciones propias del Derecho Administrativo han sido configuradas, delineadas y controladas constitucionalmente en el Perú, para lo cual repasa la más importante jurisprudencia.
The constitutionalization of administrative law
Keywords: Derecho; https://purl.org/pe-repo/ocde/ford#5.05.01